Plant spacing and pollen quantity on yield and quality of squash seeds - Lima,Márcio S. de (2003)
Squash seeds yield and quality can be improved by proper population plant spacing and the pollen quantity, which influences the pollination quality and fertilization. Nine experiments were conducted as a factorial combination of three spacing between plants (0.8 x 0.3, 0.8 x 0.6 and 0.8 x 0.9 m), two quantities of pollen (50% of an anther and another entire one) and natural insect pollination. Seed and fruit production parameters, and seed quality were evaluated. A randomized complete block design, five replications, with ten plants per plot was adopted. Larger plant spacing increased the average number of mature fruits and seed yield per plant. Seed yield was directly proportional to the amount of pollen used during pollination. Higher amounts of pollen resulted in higher seed yield per area, but the plant spacing did not affect this characteristic. Manual pollination, using a whole anther, did not differ from natural pollination in relation to seed yield and quality.